HEMATOLOGICAL ALTERATIONS IN THE AFRICAN CATFISH (Clarias gariepinus) JUVENILES EXPOSED TO SUB-CHRONIC CONCENTRATIONS OF DIAZEPAM. - OGUEJI, E. O; NWANI, C.D; IHEANACHO, S.C; MBAH, C. E; IBRAHIM, B. U (Nigerian Journal of Fisheries, 2017)
A 4-week toxicological study was conducted to ascertain the effect of diazepam drug on haematology of Clarias gariepinus Juvenile. A total of 180 (27.36±0.23cm and 197.39±2.34g) juveniles were exposed to diazepam drug at sub chronic concentrations; 2.67mg/l, 5.34mg/l, 10.68mg/l, 21.36mg/l, 42.72mg/l as treatments, and a control without diazepam substance. Blood samples were collected from each treatment on weekly basis for haematological examination. Significant decreases in red blood cells (RBC), haemologlobin count (Hb) and pack cell volume (PCV) were observed in diazepam treated groups at continued duration exposure when compared with the control. A reverse trend was observed for white blood cells. Significant increases (p˂0.05) in red cell indices were observed among diazepam treated groups compared to the control at continued duration exposure. Result for leucocyte differentials revealed that there were no significant differences (p˃0.05) among diapezam treated group compared to the control for monocytes, basophils and Eosinophils while significant differences (p˂0.05) in neutrophil and lymphocyte values were observed among treatments compared to the control. Diazepam adversely altered blood parameters of the fish.